Spaceflight Environment-Induced Variation in Root Yield and Active Constituents of Salvia miltiorrhiza - Peng, Liang; Ru, Mei; Wang, Kunru; Li, Bo; Wang, Yancui; Xia, Pengguo; Liang, Zongsuo (Planta Medica, 2014)
Salvia miltiorrhiza is a significant source of bioactive compounds providing human health effects. Here, we surveyed root yield and the active constituentsʼ divergences of second generation S. miltiorrhiza (SP2) responding to a spaceflight environment. High-performance liquid chromatography was conducted for the comprehensive constituentsʼ characterizations of 28 SP2 lines (224 individuals) and the ground control (eight individuals). The results showed that the mean fresh and dry weight of roots ranged from 116 to 172 g and 25 to 119 g, respectively, in SP2 lines. In addition, the mean contents of four tanshinone compounds (tanshinone I, tanshinone IIA, cryptotanshinone, and dihydrotanshinone I) of 28 SP2 lines varied from 0.32 to 1.04 mg · g−1, 0.47 to 2.39 mg · g−1, 0.25 to 1.60 mg · g−1, and 0.53 to 1.67 mg · g−1, respectively. Except for salvianolic acid B, which varied drastically from 72 % to 201 % of the ground control treatment, the other six phenolic acid contents of the 28 SP2 lines all increased after spaceflight. Principal component analysis was performed to obtain an overview of the distribution of all samples, and score plots clearly separated the SP2 accessions from ground controls. Moreover, a positive relationship was observed between tanshinone I and tanshinone IIA (r = 0.790, p < 0.01), and rosmarinic acid was positively correlated with salvianolic acid B (r = 0.728, p < 0.01). In conclusion, this study demonstrated that a spaceflight environment induced SP2 accessions remarkably in the variation of root yield and active constituent content.
Keywords: Salvia miltiorrhiza; Lamiaceae; spaceflight; yield; active constituents; principal component analysis